The Impact of Clarity on College Student Stamina: An Econometric Analysis - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between clarity and vigor in first-year university students in Montería, based on a quantitative approach based on a simple linear regression model. It is based on the premise that a higher level of clarity in academic processes and in the organization of learning positively influences the vigor of students, understood as the energy, endurance and motivation with which they face their studies. From the analysis of a sample of 233 university students, it was found that clarity has a positive and significant effect on vigor, with a coefficient of 0.1707 (p < 0.01). The validation of the model through statistical tests confirms compliance with the linear regression assumptions, guaranteeing the reliability of the results. It is concluded that students who perceive greater clarity in their academic environment have higher levels of vigor, which suggests the importance of structuring pedagogical strategies that favor organization, effective communication and planning in university education.